Connected Education Innovation Program: an analysis in light of the Meaningful Connectivity concept - Santos, Priscila Costa; Espíndola, Marina Bazzo de; Almeida, Maria Elizabeth Bianconcini de (Revista Educação e Cultura Contemporânea, 2024)
This theoretical essay analyzed the Connected Education Innovation Program through the lens of the concept of meaningful connectivity and the triad of curriculum, assessment, and research. Meaningful connectivity goes beyond basic internet access, requiring adequate speed, unlimited data, and appropriate devices to ensure productive use and support educational and civic objectives. Criteria such as speed, devices, data, and usage frequency were evaluated to determine whether the program meets the demands of the Brazilian educational context. The program, an initiative of the Ministry of Education, seeks to promote the pedagogical use of digital technologies, train teachers and school managers, and improve infrastructure. Despite advances, challenges persist: speeds below the recommended level, the absence of individual devices, and a lack of unlimited data hinder digital inclusion. Furthermore, the curriculum, assessment, and research triad was undervalued, highlighting conceptual and structural challenges. Overcoming these barriers requires treating digital inclusion as a basic right, integrating critical pedagogical practices, and promoting full digital citizenship.